Toxicologia dos cosméticos - Chorilli, Marlus [UNESP]; Scarpa, Maria Virgínia [UNESP]; Leonardi, Gislaine Ricci; Franco, Yoko Oshima (My University, 2007)
Although not desirable, cosmetic products can cause some adverse effects in me user. Such effects can be due bom to individual factors and by inadequate use. So, the safety evaluation must precede the placement of the cosmetic product in the market. Once the consumer has free access to cosmetic product, it must be safe in normal conditions or reasonably previsible of use. Historically the evaluation tests were accomplished with animals (in vivo) but, at the moment, some research centers have been adopting new alternatives (in vitro) in order to replace me tests with animals. This article emphasizes me necessity of accomplishing toxicity assays for personal hygiene products, cosmetics and perfumes, an also presents the tests in vivo and in vitro used, approaching the necessity of alternative methods to the assays in vitro in the evaluation of security of them.
Cosmetics toxicology
Keywords: Alternative methods; Cosmetics; In vivo methods; Toxicity; cosmetic; cosmetic industry; emulsion; food and drug administration; hygiene; mutagenicity; nonhuman; photosensitivity; phototoxicity; review; risk assessment; skin irritation; teratogenicity; toxicity testing